Preliminary study on the development of guayabano (Annona muricata) chew - Datiles , Joan B. (2001.)
Three formulations with different puree to water ratio such as 400/500 g (F1), 500/500 g (F2) and 600/500 g (F3) were prepared and analyzed after production and during storage.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Guayabano; Annona muricata